The semantic development of some Roman ethical concepts in the second century B.C. : based on contemporary literary epigraphical and numismatical evidence - Van Gysen, Nico (Classical Studies, 2016)
In almost any general study of Roman history, references can be found to the character of the Roman people. Roman character forms the explanation of their conquests, the justification of their empire. Roman character and its resultant code of behaviour influenced early Christian writers; Roman ethical concepts form the firm foundation of Western civilization. Augustine used the Roman spirit of sacrifice for the common good as an example for the inhabitants of the City of God. Dante claims that the Roman people were ordained by nature for empire by foregoing their own advantage to secure the public safety of mankind. Many modern authors echo these sentiments: R.H. Barrow says: 'His virtues are honesty and thrift, forethought and patience, work and endurance and courage, self-reliance, simplicity and humility in the face of what is greater than himself.' He even gives a 'catalogue of virtues' which Romans regarded as characteristically Roman throughout their history. Religio, pietas, officium, gravitas, discipline, industria, virtus, clementia, mores maiorum are the character traits of the Roman people. F.R. Cowell gives a much shorter list (pietas, virtus, gravitas) but he at least warns his readers that these are the virtues which Cicero regarded as typically Roman. Cowell regards them as symptoms of Cicero's enthusiasm for the good old days, and he adds: 'we have learnt in our own day that there are few more misleading imaginative exercises than that of generalizing about the supposed character of so large and complete an organism as a nation.' The purpose of this study is to investigate some of these concepts, their development and importance in early Roman sources. The approach will be ideogrammatic, but to make more general conclusions possible the group of concepts has to be fairly large and this of course means sacrificing depth for the sake of breadth.